Displacement of PAMAM-Au via acoustic streaming on an electrochemical immunosensing platform - Syamila, Noor; Hamzah, Amir Syahir Amir; Laurell, Thomas; Sulaiman, Yusran; Ikeno, Shinya; Siang Tan, Wen; Ahmad Tajudin, Asilah (Institute of Physics, 2024)
The displacement of an electroactive monitoring agent, i.e., polyamidoamine dendrimers encapsulated gold nanoparticles (PAMAM-Au) upon the presence of a target antibody via acoustic streaming has been studied. Acoustic streaming has been used to improve the mass transfer and reduce the sample incubation rate, thus this study investigated its ability in enhancing the PAMAM-Au displacement efficiency of our immunosensor. For this purpose, the bio-nanogate components of maltose-binding protein carrying the antigenic determinant (MBP-aD) of hepatitis B surface antigen (HBsAg) as a bioreceptor was functionalized, followed by the monitoring agent i.e. PAMAM-Au on the electrode prior to the incubation with targeted anti-hepatitis B surface antigen (anti-HBsAg) antibody. The modified electrode was then coupled with a piezotransducer and connected to the signal transducer to induce acoustic streaming upon sample incubation. Under optimal acoustic actuation, the sample incubation time has been reduced from 20 min to 8 min via the enhancement of PAMAM-Au displacement induced by acoustic streaming. The result also demonstrated that the specificity and selectivity of the sensing platform under acoustic actuation are comparable to the static incubation in detecting the targeted antibody.